How to Accept Yourself? 9 Tips to Love Yourself - Platon, Marilena Cristina (New Trends in Psychology, 2024)
In our journey to happiness and personal fulfillment, one of the most important destinations is self-love. It’s a delicate and often challenging process, but essential to building a healthy relationship with ourselves and others. In this article, we will explore what it means to accept ourselves, the connection between self-esteem and self-acceptance, the importance of self-love, and offer nine practical tips to cultivate love and respect for ourselves.